Predição farmacocinética e efeito protetor do análogo sintético da curcumina (1E,4E)-1,5-DIFENILPENTA-1,4-DIEN-3-ONA na lesão celular renal causada por gentamicina e na interação com NADPH Oxidase-4 - Alexandre, Felipe Ramos (2023)
Aminoglycosides are a class of antimicrobial drugs useful in the treatment of infections caused by Gram-negative bacteria. However, the use of these drugs, including gentamicin (GT), is limited due to the occurrence of nephrotoxicity. Therefore, the development of nephroprotective drugs may be a valid strategy for preventing nephrotoxicity associated with this drug. Curcumin is a compound extracted from turmeric (Curcuma longa L.) that, despite having various bioactivities, has low bioavailability. In this sense, synthetic analogs have been developed, such as the derivative (1E,4E)-1,5-diphenylpent-1,4-dien-3-one (DBA), which has a monocarbonyl group in the open chain and no substitutions in the rings. Thus, the present study aimed to analyze the pharmacokinetic characteristics and protective effect of DBA on gentamicin-induced renal cell injury in an in vitro model, as well as the theoretical interactions between DBA and the enzyme NADPH oxidase-4 (NOX4). The physicochemical and predictive pharmacokinetic characteristics were investigated using in silico computational methods and compared to those observed for curcumin. HK2 cells were exposed to GT and subjected to pre- and post-treatment with DBA to evaluate the protective effect using the MTT reduction assay. Oxidative stress was measured by determining the levels of thiobarbituric acid reactive substances (TBARS) and reduced glutathione (GSH), and changes in mitochondrial function were assessed by staining with rhodamine 123. The in silico interaction of DBA with NOX4 was evaluated by molecular docking. The curcuminoid DBA showed good pharmacokinetic characteristics in the in silico assays. In the in vitro assays, the curcuminoid DBA improved cell viability and transmembrane potential at concentrations of 31.25 and 15.62 μM. Decreased production of reactive oxygen species and mitochondrial depolarization were observed, along with increased GSH and decreased TBARS. Thus, the curcuminoid DBA protected HK2 cells against oxidative damage caused by GT. In the molecular docking assay, DBA interacted in a region similar to the inhibitor apocynin, with a better interaction energy. In conclusion, DBA exhibited a protective effect on gentamicin-induced renal cell injury, reducing mitochondrial damage and oxidative stress. This effect may be related to the inhibition of NOX4.